Analisis Pembangkit Listrik Hybrid Surya-Bayu untuk Pembelajaran Praktis - Tharo, Zuraidah; Siti Anisah; Rahman, Fatur (Universitas Medan Area, 2024)
A hybrid solar-wind power plant is a combination of two renewable energy sources, namely solar and wind power, used to generate electricity. This research aims to analyze the performance and efficiency of the hybrid solar-wind power generation system as a practical learning tool. The research methodology involves collecting performance data from solar panels and wind turbines, as well as analyzing the integration of these two energy sources. The results show that this hybrid system can improve the stability and continuity of the electricity supply compared to using a single energy source. This is evidenced by the increase in hybrid plant efficiency to 33.78%, compared to the solar panel efficiency of only 15.589%, resulting in an efficiency increase of 18.191%. Additionally, the carbon emission reduction in the hybrid system is 94.42%. The implementation of the hybrid solar-wind power plant as a learning tool provides students with a deeper understanding of renewable energy technology applications and encourages innovation in the field of sustainable energy.